Syntactic Comprehension in Patients with Amyotrophic Lateral Sclerosis - Kentarou Yoshizawa; Nao Yasuda; Michinari Fukuda; Yumi Yukimoto; Mieko Ogino; Wakana Hata; Ikuyo Ishizaka; Mari Higashikawa (Behavioural Neurology)
Recent neuropsychological studies of patients with amyotrophic lateral sclerosis (ALS) have demonstrated that some patients have aphasic symptoms, including impaired syntactic comprehension. However, it is not known if syntactic comprehension disorder is related to executive and visuospatial dysfunction. In this study, we evaluated syntactic comprehension using the Syntax Test for Aphasia (STA) auditory comprehension task, frontal executive function using the Frontal Assessment Battery (FAB), visuospatial function using Raven’s Coloured Progressive Matrices (RCPM), and dementia using the Hasegawa Dementia Scale-Revised (HDS-R) in 25 patients with ALS. Of the 25 patients, 18 (72%) had syntactic comprehension disorder (STA score < IV), nine (36%) had frontal executive dysfunction (FAB score < 14), six (24%) had visuospatial dysfunction (RCPM score < 24), and none had dementia (HDS-R score < 20). Nine of the 18 patients with syntactic comprehension disorder (50%) passed the FAB and RCPM. Although sample size was small, these patients had a low STA score but normal FAB and RCPM score. All patients with bulbar onset ALS had syntactic comprehension disorder. These results indicate that it might be necessary to assess syntactic comprehension in patients with bulbar onset ALS. The implications of these findings are discussed in relation to the pathological continuum of ALS.